THE FACTORS THAT AFFECTING THE DEMAND OF FISH SEEDS AT UPT BALAI BENIH IKAN (BBI) KOTO BARU SUB-DISTRICT DHARMASRAYA REGENCY WEST SUMATRA PROVINCE - Sudarno, Aulia Moriska; Bathara, Lamun; Hamid, Hamdi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Fish seed are the main production input for fish cultivation business. This research aimed to find out the trends in the development offish seed demand Tilapia (Oreochromis niloticus) having a size of 3-5 cm and to find out the factors affecting the demand of fish seed themselves (Oreochromis niloticus). The research was conducted in February until March 2019 at UPT Balai Benih Ikan (BBI) in Koto Baru Sub-District, Dharmasraya Regency, West Sumatera Province. The method used was the survey method. The population in this study were that consumers made a demand for fish seed having been provided by UPT Balai Benih Ikan (BBI). Sampling conducted was by accidental sampling. The number of respondents was 35 individu. Data collection techniques used were observation and questionnaire. Meanwhile, the data analysis technique used was SPSS 20.0 with the linear multiple regression statistical analysis. The results of this study showed that the trend of the development of demand for Tilapia fish seed (Oreochromis niloticus) having a measure 3-5 cm in 5 periods (2019-2023) was getting a decrease in demand. The demand conditions were influenced by the fish seed price factor (X1), transportation costs (X2) and fish seed size (X3). The coefficient of determination (r2) showed the effect of independent variables simultaneously at 40.2%. Consecutively the factors greatly affecting the demand were transportation costs (X2) of 0.001, seed prices (X1) of 0.002, and fish seed size (X3) of 0.003. Keywords: Fish seed, Development, Demand, and Dharmasraya.